COMPARING ENVIRONMENTAL MANAGEMENT AND CITIES SUSTAINABILITY AS A BASIS FOR SUSTAINABLE DEVELOPMENT IN NIGERIA - Eya, Adamu Musa; Sinniah, Gobi Krishna; Junaidu, A. M.; Zubairu, Mustapha (PLANNING MALAYSIA, 2022)
Nigerians Over the last decade, there has been a greater awareness of the complex relationship that exists between the growth of cities and the state of the environment. However, much work remains to be done to improve the quality of cities’ environmental conditions to achieve developmental goals. Like most developing countries, faces environmental management challenges such as waste management, water pollution, air quality, carbon emissions, conservation and preservation of nature, climate change, city transportation, housing development, park, and gardens. The evidence suggests that adequate measures have not been taken to balance development goals with the need to maintain environmental quality. This paper investigates the strategies associated with environmental management and the success of sustainable cities. The Likert scale was used in the study. The study also used simple regression and Chi-square goodness of fit to determine the relationship between the study variables. According to the findings, the critical p-value of 9.487729 is greater than the computed value x2 0.1844. The coefficient of r 0.0001 is greater than the critical value of 9.487729. The study discovered a strong link between environmental management and the long-term viability of cities. This research will provide a foundation for stakeholders, government, and environmental management challenges.